Nonspecific symptoms of intussusception - Bob Wahyudin; Nassir Abbas; Setia Budi; Azis Tanra (Indonesian Pediatric Society Publishing House, 2016)
This paper reports 2 cases of intussusception with nonspecific symptoms.